God, Spirit, and Sacrifice: Traditional Mara Beliefs and Their Significance for Modern Christianity - Chozah, Telung (Asia journal of theology, 2025)
This article explores the profound connections between the traditional Mara concepts of God and spirit and their influence on daily life, as well as their intersections with Christian theology. It examines how Mara rituals, rooted in their beliefs about Khazȏhpa, the benevolent creator and sustainer of life, serve to protect individuals from malevolent influences and ensure their well-being. The study highlights that Khazȏhpa bears significant similarities to the Christian understanding of God, particularly in terms of creation, preservation of life, and divine benevolence. Furthermore, it reveals that Thlaphapa, the benevolent spirit in the Mara tradition, parallels the Christian Holy Spirit, sharing attributes of omnipresence and omnipotence. Overall, this article demonstrates how traditional Mara beliefs and Christian theology intersect and complement each other, offering valuable insights into the integration of spiritual practices across cultural and religious boundaries.